Peningkatan Keterampilan Anggota PKK Desa Banyumas Kecamatan Kerkap Kabupaten Bengkulu Utara Dalam Pengolahan Air Kelapa - Raisawati, Tatik; Yuni Indah; Hania Sumarni; Linda Astuti; Parwito, Parwito (Jurnal Pengabdian, 2025)
The village of Banyumas has resources in coconut trees, but their utilization is not yet optimal. The fruit of the coconut is only taken for the flesh, while the coconut water is discarded and becomes waste. Coconut water has not been utilized into economically valuable products by the community in Banyumas village, Kerkap district, North Bengkulu regency. Coconut water can be utilized to produce economically valuable products such as nata de coco, syrup, and soy sauce. The aim of the training activities in this Community Service program is to foster innovation and enhance the participants' knowledge about processing coconut water into economically valuable products, so that it can later increase the income for the villagers who develop this scientific innovation. The training on coconut water processing in Banyumas Village uses lecture and practical methods. The result of this coconut water processing training is that participants acquire information, skills, and knowledge about how to make nata de coco, syrup, and soy sauce from coconut water.